The Influence of Investment, Population, Labor, Education, and Household Consumption on Economic Growth in Bali Province - Mohamad Suryadi; Ni Nyoman Reni Suasih; Ida Bagus Putu Purbadharmaja; I Nyoman Mahaendra Yasa (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The economic development of a region is essentially an activity that is carried out consciously and continuously to realize a better situation together and continuously. Over time, changes in the economy in a region can prove real changes. This study aims to: 1) analyze the effect of investment, population, labor, education, and household consumption simultaneously on district / city economic growth in Bali Province. 2) analyze the effect of investment, population, labor, education, and household consumption partially on the economic growth of regencies / cities in Bali Province. The data used is panel data that combines cross section and time series, which is a combination of 9 districts / cities in Bali Province with a twelve-year analysis period, 2011-2022, with a total of 108 observations. The analysis technique in this study used descriptive analysis and inferential analysis (multiple linear regression). The results showed that: 1) investment, population, labor, education, and household consumption simultaneously affect the economic growth of districts / cities in Bali Province. 2) investment partially negatively affects the economic growth of regencies / cities in Bali Province. 3) population partially has a positive effect on the economic growth of regencies / cities in Bali Province. 4) labor partially has a positive effect on district / city economic growth in Bali Province. 5) education partially has a positive effect on the economic growth of districts / cities in Bali Province. 6) Household consumption partially has a positive effect on district / city economic growth in Bali Province.